Digital Business Ecosystem Strategy in Aviation : Interline Cooperation and Operational Efficiency with the Moderating Role of Digital Integration and Operational Challenges - Muhammad Awaluddin (Journal of Digital Business and Global Economy, 2026)
This study examines the role of interline cooperation in enhancing operational efficiency within the aviation industry from a digital business ecosystem perspective. It specifically investigates how digital integration strengthens this relationship and how operational challenges may constrain it. A qualitative case study approach was employed, using semi-structured interviews with eight aviation professionals involved in operations, network planning, and interline coordination. The data were analyzed using thematic analysis with an NVivo-style coding process. The findings reveal that interline cooperation contributes to operational efficiency by enabling network expansion, improving resource utilization, and reducing operational redundancies. The results also indicate that digital integration plays a significant role in enhancing coordination through real-time data exchange and system interoperability, thereby strengthening the effectiveness of interline cooperation. However, several operational challenges such as system incompatibility, coordination complexity, and demand mismatch were found to limit these efficiency gains. This study contributes to the literature by integrating interline cooperation, digital integration, and operational challenges within a digital business ecosystem framework to explain operational efficiency. It also provides practical insights for airline managers to optimize collaborative strategies through improved digital alignment and operational coordination.